The neurodiversity concept was developed collectively: An overdue correction on the origins of neurodiversity theory - Botha, Monique; Chapman, Robert; Giwa Onaiwu, Morénike; Kapp, Steven K; Stannard Ashley, Abs; Walker, Nick (Autism : the international journal of research and practice, 2024)
We, an international group of autistic scholars of autism and neurodiversity, discuss recent findings on the origins of the concept and theorising of neurodiversity. For some time, the coinage and theorising of the concept of ‘neurodiversity’ has been attributed to Judy Singer. Singer wrote an Honours thesis on the subject in 1998, focused on autistic activists and allies in the autistic community email list Independent Living (InLv). This was revised into a briefer book chapter, published in 1999. Despite the widespread attribution to Singer, the terms ‘neurological diversity’ and ‘neurodiversity’ were first printed in 1997 and 1998, respectively, in the work of the journalist Harvey Blume, who himself attributed them not to Singer but rather to the online community of autistic people, such as the ‘Institute for the Study of the Neurologically Typical’. Recently, Martijn Dekker reported a 1996 discussion in which one InLv poster, Tony Langdon, writes of the ‘neurological diversity of people. i.e. the atypical among a society provide the different perspectives needed to generate new ideas and advances, whether they be technological, cultural, artistic or otherwise’. Going forward, we should recognise the multiple, collective origins of the neurodiversity concept rather than attributing it to any single author. Lay abstract This letter discusses the origins of the concept and theory of neurodiversity. It is important to correctly attribute concept and theories to the people who developed them. For some time, the concept of neurodiversity has primarily been attributed to one person, Judy Singer. We consider the available evidence and show that the concept and theory in fact has multiple origins. We draw particular attention to recent archival findings that show the concept of ‘neurological diversity’ was being used years earlier than previously thought. ‘Neurodiversity’ means the same thing as ‘neurological diversity’ and does not change the theory in any way. We conclude that both the concept of neurological diversity or neurodiversity, and the body of theory surrounding it, should be understood as having been collectively developed by neurodivergent people.